ANALISA DAN PERANCANGAN SISTEM INFORMASI PENCATATAN DAN PELAPORAN KEUANGAN SEKOLAH BERBASIS CLOUD COMPUTING - Dosma P. Sibuea (TeIKa, 2017)
The financial recording system is very important for an organization such as a school. The existence of a good record will help the school access history of financial transactions data and facilitate in making financial statements. An information system is needed to help recording the financial transactions of the school, both student transactions and other transactions conducted in schools. The purpose of this research is to design a financial information recording and reporting system of school based on cloud computing that can help the school in recording every transaction that occurs in school and make it easier to create financial statements both monthly and yearly. With the use of cloud computing will help the school in implementing the information system mainly related to the cost of infrastructure procurement constraints. In the future, it is expected that this information system can be developed with mobile platform so it is easier for every user in using it.